2018
DOI: 10.1021/acs.langmuir.8b00562
|View full text |Cite
|
Sign up to set email alerts
|

Designs of Zwitterionic Interfaces and Membranes

Abstract: Zwitterionic materials are the latest generation of materials for nonfouling interfaces and membranes. They outperform poly(ethylene glycol) derivatives because they form tighter bonds with water molecules and can trap more water molecules. This feature article summarizes our laboratory's fundamental developments related to the functionalization of interfaces and membranes using zwitterionic materials. Our molecular designs of zwitterionic polymers and copolymers, sulfobetaine-based, carboxybetaine-based, or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 119 publications
1
45
0
Order By: Relevance
“…Through the SIP, the structure parameter (S) was reduced about 43% compared to the controlled membrane because of the superhydrophilicity of the zwitterionic moieties. Meanwhile, the antibacterial property of the zwitterionic functionalized membrane significantly improved as expected [75], where the amount of attached E. coli was reduced from 4810 cell/mm 2 to 352 cell/mm 2 . Besides, the protein foulants BSA, and lysozyme was used to investigate the performance.…”
Section: Second Interfacial Polymerization (Sip)supporting
confidence: 72%
“…Through the SIP, the structure parameter (S) was reduced about 43% compared to the controlled membrane because of the superhydrophilicity of the zwitterionic moieties. Meanwhile, the antibacterial property of the zwitterionic functionalized membrane significantly improved as expected [75], where the amount of attached E. coli was reduced from 4810 cell/mm 2 to 352 cell/mm 2 . Besides, the protein foulants BSA, and lysozyme was used to investigate the performance.…”
Section: Second Interfacial Polymerization (Sip)supporting
confidence: 72%
“…In recent years, the zwitterionic polymers have become a promising material in membrane research for development of a universal antifouling and antibacterial membrane [32][33][34][35]. Both the cationic and anionic moieties of the zwitterionic materials on the membrane surface can be used to control the superhydrophilicity, biocompatibility, and non/fouling ability [36].…”
Section: Introductionmentioning
confidence: 99%
“…Since the ion pairs can trap significant amount of free water molecule by electrostatic interactions, a denser and tighter hydration layer can be formed on the membrane surface layer [37]. Several types of zwitterionic copolymers in this aspect have been synthesized and investigated to adapt different surface chemistry and application [33]. An et al reported the homemade zwitterionic monomer N-aminoethyl piperazine propane sulfonate (AEPPS) incorporated nanofiltration membrane with improved water flux (84%) and rejection (~97%) with K 2 SO 4 in the feed stream [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, polyzwitterions represent a special subclass of polyampholytes featuring very particular properties, including high polarity (and thus often high hydrophilicity), anti-polyelectrolyte behavior and stimuli-responsiveness [1,2,3]. By virtue of this exceptional property profile, they have increasingly attracted interest due to their great potential for diverse applications, such as biocompatibilization, cryo preservation, lubrication, smart self-assembly, and low-fouling surfaces in aqueous environments [4,5,6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%